A comprehensive review on expansion planning: Models and tools for energy policy analysis. (December 2018) - Gacitua, L.; Gallegos, P.; Henriquez-Auba, R.; Lorca, Á.; Negrete-Pincetic, M.; Olivares, D.; Valenzuela, A.; Wenzel, G.
Abstract: Energy systems are quickly evolving through the development of new technologies and the emergence of new operational and market design paradigms. In particular, the global push for sustainability is driving the transition towards a pronounced redesign. In fact, renewable energy integration is occurring at a massive scale, and several other exciting developments are finding their place in modern energy systems, such as distributed energy resources, demand response, energy storage technologies, and local energy markets. In this dynamic context, the process of energy policy design and implementation has found new challenges, and in supporting this key process, expansion planning models and tools can play an essential role. For example, these models can be employed to estimate the impact of a multitude of policy instruments. Thus, there is a wide interest in these tools and a variety of such models, as evidenced by a rich literature and a fast-paced evolution of this research area. Motivated by this, this work presents a comprehensive and up-to-date review on expansion planning models and tools with emphasis on their application to energy policy analysis. In particular, this paper reviews the most significant policy instruments, with an emphasis in renewable energy integration, the optimization models that have been developed for expansion planning, and existing decision-support tools for energy policy analysis. Finally, this paper also discusses the trends in the literature and the most pressing current challenges in the development and use of expansion planning models for energy policy analysis. Abstract : Highlights: Provides a comprehensive and up-to-date overview on expansion planning models. Reviews the most significant policy instruments with an emphasis in renewable energy integration. Describes the salient features of using expansion models on energy policy analysis. Discusses the future trends and challenges of smart grid technologies on expansion models.